2012
DOI: 10.1117/12.921473
|View full text |Cite
|
Sign up to set email alerts
|

Detection in urban scenario using combined airborne imaging sensors

Abstract: The EDA project "Detection in Urban scenario using Combined Airborne imaging Sensors" (DUCAS) is in progress. The aim of the project is to investigate the potential benefit of combined high spatial and spectral resolution airborne imagery for several defense applications in the urban area. The project is taking advantage of the combined resources from 7 contributing nations within the EDA framework. An extensive field trial has been carried out in the city of Zeebrugge at the Belgian coast in June 2011. The Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
(3 reference statements)
0
7
0
Order By: Relevance
“…However, interpreting or post-processing the detected anomalies requires considerable effort because of the great diversity of materials in the urban environment. 1 Furthermore, using a single image exploits only part of the large amount of information that could be gathered by imaging an area successfully over time, and which combines data from different imaging sensors.…”
Section: Continued On Next Pagementioning
confidence: 99%
See 1 more Smart Citation
“…However, interpreting or post-processing the detected anomalies requires considerable effort because of the great diversity of materials in the urban environment. 1 Furthermore, using a single image exploits only part of the large amount of information that could be gathered by imaging an area successfully over time, and which combines data from different imaging sensors.…”
Section: Continued On Next Pagementioning
confidence: 99%
“…Analyzing data from the trial, we considered many different applications for remote sensing data, reporting preliminary results in 2012. 1 We checked the quality of the remotely sensed hyperspectral data using ground truth measurements (information collected at the site) and modeling of radiative transfer (the movement of radiation with regard to emission, absorption, and scattering). We compared measured spectra extracted from a hyperspectral image with simulated spectra from ground and atmospheric measurements and the MODTRAN computer program (MODerate resolution atmospheric TRANsmission).…”
mentioning
confidence: 99%
“…DUCAS started in 2010 and will end in 2013. For the scope of DUCAS an extensive data set of hyperspectral and high spatial resolution data was generated in a common field trial in Zeebrugge, Belgium [1,2], in the year 2011. Additionally, 3D-laser data were acquired earlier to the field trial.…”
Section: Introductionmentioning
confidence: 99%
“…Different techniques are studied in a European context (DUCAS project). First study results are shown in Renhorn et al (2012) [13] and more specific on change detection in Dekker et al (2013) [14]. Combination of information from various sources and various processing techniques is the key parameter.…”
Section: Automated Processingmentioning
confidence: 99%